Formation of the first aryl zinc-hydroxy cubane, [ArZn(OH)](4) (Ar=2,4,6-(CF3)(3)C6H2) - Agnew, C; Dillon, K; Goeta, A; Thompson, A (2009)
The compound [ArZn(OH)]4 (Ar = 2,4,6-(CF3)3C6H2), formed by aggregation of the hydrolysis product of ArZnCl, has a cubane-like structure at 120 K; this is the first structurally characterised example of such a zinc(II) derivative with a simple aromatic group on Zn, and with the bridges formed by -OH rather than -OR groups. It crystallises as a hemisolvate in the triclinic system (P over(1, ̄)), with a single molecule in the asymmetric unit, together with one CHCl3 (or CDCl3) molecule per two molecules of the tetramer. © 2009 Elsevier B.V. All rights reserved.